Application of Finger Clasp Relaxation to Reduce Pain Intensity in Post Pyelolithotomy Patients at PKU Muhammadiyah Hospital Yogyakarta: A Case Study - Purbadewi, Jihan; Noviani, Wulan (Rifa'Institute, 2023)
Introduction: Nephrolithiasis or kidney stone disease is a condition in which the formation of stone-like masses in the kidneys caused by the presence of certain substances such as salts and minerals. Kidney stones can form and move through the urinary tract which includes the kidneys, bladder, and urethra. Objective: Finger grip relaxation therapy is a non-pharmacological technique for pain management that can be done independently with the aim of reducing pain by reducing muscle tension that causes pain. Method: This study adopts a descriptive method with a case study approach that focuses on nursing care. Case study subjects with one patient postoperative pyelolithotomy. Result and Discussion: Finger grip relaxation can be used as another therapy to reduce pain levels in patients who have undergone surgery for the treatment of kidney stones. Conclusion: The results of this case study showed a decrease in scale where initially patients complained of pain on a scale of 8 after three days of therapy there was a decrease to a scale of 4.